The efficacy of ophiopogonanone B in treating the cough in mice infected with Mycoplasma pneumoniae - Liu, Nan-Nan; Guo, Bai-Hui; Wang, Lei; Wang, Xiao-Xi; Wang, Xin; Meng, Yan-Li; Tang, Gui-Xin; Wang, Wei-Ming (Frontiers in Pharmacology, 2025)
IntroductionOphiopogonanone B is a potent component of Qinbai Qingfei-concentrated pills (Qinbai), a new traditional Chinese medicine developed by our hospital for the treatment of Mycoplasma pneumoniae pneumonia in children. We aim to study how ophiopogonanone B influences the expression of transient receptor potential anchor protein 1 (TRPA1), substance P (SP), and calcitonin gene-related peptide (CGRP) to treat coughing in MP-infected mice.MethodsUltra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was used to detect ophiopogonanone B. Molecular docking of ophiopogonanone B with TRPA1 was performed using Autodock Vina 1.1.2, and subsequent visualization and analysis of docking outcomes were facilitated using Pymol 2.1 and Discovery Studio. For the evaluation of the pathological structure and morphology, lung tissue sections from mice were prepared for animal experiments and subjected to hematoxylin-eosin (HE) and Masson staining. The impact of ophiopogonanone B on the protein and mRNA expression levels of TRPA1, SP, and CGRP in mouse lung tissue was assessed using immunohistochemistry and real-time polymerase chain reaction (RT-PCR).ResultsThe samples acquired through Biacore fishing, which were identified and analyzed by UPLC-Q-TOF-MS, confirmed the presence of ophiopogonanone B. This compound exhibited robust and specific binding affinity for TRPA1. Histological staining using HE and Masson techniques revealed that the lung tissue morphology and structure in the ophiopogonanone B-treated group closely mirrored those observed in the blank group. Subsequent immunohistochemistry and RT-PCR revealed a significant reduction (P < 0.01 or P < 0.05) in the proteins and mRNA expression levels of TRPA1, SP, and CGRP in the lung tissue of mice treated with high and medium doses of ophiopogonanone B.ConclusionBy decreasing the expression of TRPA1, SP, and CGRP in the lung tissues of mice afflicted with coughing due to M. pneumoniae infection, ophiopogonanone B effectively alleviated post-infection cough symptoms.